Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Kue Brownies Glowing Cake Di Mataram - Fierni Handayani; Zulkarnaen; Rosyia Wardani (Kredibel: Jurnal Ilmiah Manajemen, 2026)
This study aims to determine the role of SWOT analysis in increasing sales at the Glowing Cake Brownies Cake Shop in Mataram. The problem in this research is "whether SWOT analysis plays a role in increasing sales at Brownies Glowing Cake Cake Shops in Mataram". The research method used in this research is descriptive analysis research method, SWOT Matrix, External Factor Evaluation Matrix (Ekternal Factor Evaluation-EFE), Internal Factor Evaluation Matrix (Internal Factor Evaluation-IFE). The population and sample in this study were 10 of them are employees and owners Glowing Cake Brownies Cake Shop in Mataram. Data collection techniques used in this study were questions in the form of interviews and statements in the form of questionnaires. The results of this study indicate that currently the Brownies Glowing Cake Cake Shop in Mataram The marketing strategy implemented by the Brownies Glowing Cake Cake Shop in Mataram is providing quality products at affordable prices but also considering the maximum delivery service, making maximum use of product sales through social media. the media, and maintaining the company's image in the eyes of the public so as to increase customer loyalty and the weighted value of the Matrix Internal Factor Evaluatin (IFE Matrix) is 0.18 which states that the position of Brownies Glowing Cake Cake Shop has a strong internal position. While the weighted value of the Matrix External Factor Evaluation (EFE Matrix) is -0.1 which states that the Brownies Glowing Cake Bake Shop is in the face of the external environment the company's position is threatened.